Networking banana and plantain: INIBAP Annual Report 1998 - International Network for the Improvement of Banana and Plantain (1999)
The 66th annual report of the breeding station, for the year ending 30 June 1999, is presented. The report gives information on the 1998 commercial and base broadening sugarcane crosses, genetic gain studies, and breeding for improvement of sugar content of cane and restoration of vigour. Data are presented on variety exchange (both imports and exports), and varieties grown in Guyana, Barbados, Trinidad, St. Kitts, Central Romana, Jamaica, Belize, Guadeloupe and Martinique. (Abstract © CAB ABSTRACTS, CAB International)